2012
DOI: 10.1051/0004-6361/201219145
|View full text |Cite
|
Sign up to set email alerts
|

The AGILE monitoring of Cygnus X-3: transient gamma-ray emission and spectral constraints

Abstract: We present the AGILE-GRID (Astro-rivelatore Gamma a Immagini LEggero -Gamma-Ray Imaging Detector) monitoring of Cygnus X-3, during the period between November 2007 and July 2009. We report here the whole AGILE-GRID monitoring of Cygnus X-3 in the AGILE "pointing" mode data-taking, to confirm that the γ-ray activity coincides with the same repetitive pattern of multiwavelength emission and analyze in depth the overall γ-ray spectrum by assuming both leptonic and hadronic scenarios. Seven intense γ-ray events we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 58 publications
(117 reference statements)
4
50
0
Order By: Relevance
“…11 the 1AGLR J2033+4057/ Cyg X-3 light curve together with the 15−150 keV daily light curve from Swift/BAT (Barthelmy et al 2005). This plot is similar to those reported in Tavani et al (2009c), Bulgarelli et al (2012a), and Piano et al (2012). Here we show the 1−2-day γ-ray flare times in the Pointing mode interval described there.…”
Section: Long-term Light Curves Of Some Prominent Sourcessupporting
confidence: 92%
See 2 more Smart Citations
“…11 the 1AGLR J2033+4057/ Cyg X-3 light curve together with the 15−150 keV daily light curve from Swift/BAT (Barthelmy et al 2005). This plot is similar to those reported in Tavani et al (2009c), Bulgarelli et al (2012a), and Piano et al (2012). Here we show the 1−2-day γ-ray flare times in the Pointing mode interval described there.…”
Section: Long-term Light Curves Of Some Prominent Sourcessupporting
confidence: 92%
“…The first AGILE catalogue ) was built using data collected during the first year of operations (July 2007-June 2008, which includes half of cycle-1 of the AGILE GO (Tavani et al 2009b(Tavani et al , 2009cSabatini et al 2010;Giuliani et al 2010;Bulgarelli et al 2012a;Piano et al 2012).…”
Section: Revision Of the First Agile-grid Catalogue Based On The 23 mentioning
confidence: 99%
See 1 more Smart Citation
“…So far, the only microquasar (i.e. XRB displaying relativistic jets) firmly detected at high energies (> 100 MeV) is Cygnus X-3 (Tavani et al 2009;Fermi LAT Collaboration et al 2009) and its gamma-ray emission is related to the formation/existence of the radio jets (Piano et al 2012;Corbel et al 2012). However Malyshev et al (2013) showed there is a 4σ-level evidence of gamma-ray signal for Cygnus X-1, above 100 MeV, in 3.8 yr of Fermi-LAT data, only when the source is in the HS.…”
Section: Introductionmentioning
confidence: 99%
“…7.8), PSR J2032+4127 (2AGL J2032+4135). Furthermore, three microquasars were detected in this region with variable γ-ray emission: Cygnus X-1 (Sabatini et al 2010(Sabatini et al , 2013, Cygnus X-3 (2AGL J2033+4060, Tavani et al 2009b;Abdo et al 2009c;Bulgarelli et al 2012b;Piano et al 2012), V404 Cygni (Piano et al 2017). Cygnus X-1 and V404 Cygni are not part of this Catalog.…”
Section: The Cygnus Regionmentioning
confidence: 99%